ANALISIS PERKEMBANGAN PRAKTIK BAITUL MAAL PADA MASA DAULAH ISLAMIYAH DAN DALAM KONTEKS DI INDONESIA - Risa Sari Pertiwi; Sri Herianingrum; Ridan Muhtadi; Mumuh Muhammad (Ulumuna: Jurnal Studi Keilsman, 2020)
Purpose of this study is to analyze the development of the Baitul Maal practice during the Daulah Islamiyah era and in the context of Indonesia. This study uses a qualitative approach was used through library research using various relevant library materials and previous literature studies. The main finding of this research is that the development of Baitul Maal during the Daulah Islamiyah period always experienced developments in terms of institutional, administrative, construction of central and local Baitul Maal sites and fiscal policy in the distribution of Baitul Maal assets. The main sources of income of Baitul Maal in the early days of Islamic development were khums, zakat, kharaj and jizyah in which the amount, duration and usage were based on the Qur'an and Hadith, while the expenditure of Baitul Maal funds during the Islamic State was focused on the public service sector. Nowadays, there are several different aspects between the Daulah Islamiyah and Indonesia which can be seen concepts, institutions, roles and functions, sources of income and types of expenditure Baitul Maal.